Expansion of a diesel plant into a hybrid power system using power pinch analysis - Rozali, N.E.M. (Italian Association of Chemical Engineering - AIDIC, 2015)
Diesel power system is one of the popular schemes for energy supply generation. It is, however, typically associated with high costs of emission control and maintenance on top of the diesel fuel cost. These limitations can be overcome by incorporating renewable energy technologies such as wind turbines and solar PV along with the existing diesel station. Hybrid systems provide cleaner and reliable power supply, and can be more cost-effective than sole diesel systems. This paper assesses the feasibility of expanding an existing diesel power plant into a hybrid power system (HPS) using Power Pinch Analysis (PoPA). An HPS configuration developed with PoPA methodology can provide optimal solar and wind electricity supplies while minimising the diesel runtime. Results show that an HPS that combines solar and wind system with diesel power generation can provide significant diesel fuel savings while satisfying the demands at a reasonable cost. Copyright Â© 2015, AIDIC Servizi S.r.l.,.